Transanal total mesorectal excision of giant villous tumor of the lower rectum with McKittrick–Wheelock syndrome: a case report of a novel surgical approach - Masahiko Fukase; Hiroshi Oshio; Sho Murai; Tomomi Kawana; Yusuke Saito; Emiko Kono; Yukiko Oshima; Gen Yunome; Shin Teshima; Masaaki Ito (Surgical Case Reports, 2019)
Abstract Background McKittrick–Wheelock syndrome (MKWS) is caused by a villous tumor of the rectosigmoid colon with hypersecretion of mucus containing electrolytes. Complete resection of the tumor is needed to cure this disease. Transanal total mesorectal excision (TaTME) is currently a promising treatment for lower rectal tumor because of the reliability of its resection margin especially in bulky tumor. We present this first case report of a TaTME for MKWS with a lower rectal tumor. Case presentation An 81-year-old woman was admitted to our hospital with diarrhea and acute renal failure. Computed tomography and magnetic resonance imaging examinations revealed an 80-mm-sized enhanced tumor located in her lower rectum without lymph node swelling and distant metastasis. A giant villous tumor secreting mucus was seen in the lower rectum to the anal canal during colonoscopy. The result of tumor biopsy was adenocarcinoma. To preserve the anal function and ensure distal margin, we chose TaTME for curative resection. After improving the electrolyte imbalance, TaTME was performed successfully and R0 resection was achieved. There was no sign of recurrence or electrolyte depletion for 1 year after the surgery. Conclusion TaTME could be a promising surgical approach for giant villous tumor with MKWS in the lower rectum.